E-GOVERNMENT IMPLEMENTATION IN THE E-ORDER SYSTEM IN THE DEVELOPMENT OF SMEs IN THE ADMINISTRATIVE CITY OF SOUTH JAKARTA - Asropi, Asropi (Jurnal Ilmu Administrasi Negara, 2023)
Study this aims for identify and understand urgency management application e-Order or online market for goods and services public for speed up SMES growth in DKI Jakarta Province. The program aims to increase growth economy and opportunity work for SMESs DKI Jakarta Province with provide marketing online. Website development is one of the political strategy and development strategy e-government national , that is implementation systematic development _ through realistic and measurable steps Government website development area is the first from four layers ( web presence , interaction , transaction and transformation / integration ) within stages development Indonesian e-government for possible Indonesian people with easy access information government area and participate in development Indonesian democracy through online media. Study this use approach qualitative through interviews and studies library, Study this showing several Thing that is first System application e-Order this is breakthrough innovative BPPBJ (Service Agency Procurement Goods and Services) Government DKI Jakarta Province Second, System Application e-Order is connecting application _ activity purchase SMES products (as supplier) with agency government province in DKI Jakarta.